Clinical evaluation of periodontal status associated with class II direct posterior restorations - Preliminary clinical study - Andreea Ciurea; Iulia Cristina Micu; Alexandra Roman; Daniela Condor; Andrada Soancă (Amaltea Medical Publishing House, 2020)
Aim. This clinical study aimed to evaluate the following periodontal parameters: plaque indices, bleeding indices, probing depth and attachment loss, for class II direct posterior restorations. Material and method. The direct posterior restorations were performed with two ormocer materials, Admira Fusion X-tra® (Voco, Cuxhaven, Germania) and Admira Fusion® (Voco Cuxhaven, Germania), through two different methods, bulk fill technique and proximal wall restoration technique. The periodontal parameters were followed in 4 different moments, over a period of 3 months. Results. At the evaluation of plaque indices and bleeding indices, no significant differences were observed between the 2 studied groups. In both of the followed groups, group I and group II, the values for plaque and bleeding indices were decreased during the evaluation period. The values of probing depth and attachment loss did not change at any of the evaluation moment. Conclusions. Ormocer materials and restoration techniques used in this study did not negatively influence the evaluated periodontal parameters.